Refractory otitis media: An unusual presentation of childhood granulomatosis with polyangiitis. Issue 3 (28th January 2013) - Uppal, Preena; Taitz, Jonny; Wainstein, Brynn; Soma, Marlene; Belessis, Yvonne; Gray, Paul
Abstract Childhood granulomatosis with polyangiitis (cGPA), previously known as Wegener's granulomatosis, is a rare, potentially fatal necrotizing vasculitis, the symptoms of which overlap with infection. We present a 16‐year‐old girl who, following 6 months of treatment for persistent middle ear effusion with progressive sensorineural hearing loss, developed rapidly progressing pneumonia, with pleural effusion, and multiple cavitatory lung lesions. Investigations demonstrated high titer c‐ANCA and nasal septal biopsy confirmed the diagnosis of cGPA. This case highlights the difficulty in diagnosing cGPA and the potentially life‐threatening consequences of failing to do so. Pediatr Pulmonol. 2014; 49:E21–E24. © 2013 Wiley Periodicals, Inc.